Experimental investigation of steel coiled tubes performance under cyclic bending - Lagat, Christopher; Roufail, R.; Evans, Brian; Soe, S. (2014)
Research is currently being undertaken in Australia to develop new drilling technologies for deep mineral exploration. The Deep Exploration Technologies Cooperative Research Centre (DET CRC) has carried out a comprehensive review of the available drilling technologies in the market. Following the study, coiled tube drilling technology has been suggested as a faster and cheaper method than conventional pipe drilling. This is primarily due to its smaller footprint relative to the standard rotary method, ease of unit mobility, less operating personnel, faster rate of penetration, and faster rig up and rig down times. The steel coiled tubing technology has traditionally been used in the petroleum industry. While there have been several attempts to evaluate the performance of coiled tubes in the oil and gas industry, limited or no attempts have been made to assess its performance in deep hard rock mineral exploration drilling. Therefore, DET CRC is in the process of re-designing the coiled tube rig approach to enable fast and efficient drilling of deep micro-holes in hard rocks. Cyclic bending of the coiled tubing past the yield strength point of the material leads to progressive weakening of the tube, which accordingly leads to rapid reduction of the tube service life [1]. Hence fatigue is an important parameter that needs to be considered in material selection for coiled tube and rig design. A bending machine was designed and manufactured to evaluate the fatigue bending strength of conventional HSLA steel tubes. The machine is capable of measuring and recording the bending/flattening resistant forces of the tubes along with the number of bend/flatten events. It can also measure the strain applied on the tube if needed. In this study, several HSLA steel grades and thicknesses of coiled tubes were tested for fatigue bending strength. Fatigued and non-fatigued tubes had their mechanical property alteration tested using tensile test methods. This paper presents the fatigue bending machine. The machine is designed to test most material types of coiled tubes. The paper also reports results of the cyclic bending experiments that were performed on selected grades and sizes of conventional HSLA steel coiled tubes. The paper complements and enhances the understanding of the performance of conventional coiled tube material under fatigue bending conditions.